SIFAT FISIK DAN MEKANIK PAPAN PARTIKEL DARI LIMBAH PLASTIK JENIS HDPE (High Density Polyetylene) DAN RANTING/CABANG KARET (Hevea brasiliensis Muell.Arg) - Noor Mirad Sari (Jurnal Riset Industri Hasil Hutan, 2011)
The need of log increace rapidly, mean while forest product decrease, so efficiency on wood process should be done wisely, in the other hand plastic waste is uncompossed material, become an environmental problems. This research aims to determine the impact of particles of type HDPE plastic wastes and twigs/branches of rubber on some physical and mechanical properties of wood. Physical properties have been tested for water content, density, thickness, and water absorption. Although mechanical properties tests were tough Broken/Module of Rufture (MOR) and the preservation of architecture/modulus of elasticity (MOE).     The raw materials used are polyethylene of high density of waste plastic and rubber adhesive urea formaldehyde branch branch. Experimental design used the randomized Completely Design (RCD) 5 x 4, in which each treatment became much like 5 times replicated).The treatment used is the diversity of the composition of the waste of plastic of different types of polyethylene of high density provides a significant effect on the content of water, water absorption, the density and the development of thickness. With regard to the persistence and the fracture of the arch determination not to give a significant effect.Keywords: physical and mechanical properties, particle board, HDPE plastic waste, branch/twig of  rubber.